PELATIHAN OLAHAN MAKANAN DAN MINUMAN BERBAHAN JAHE EMPRIT UNTUK PKK, KARANG TARUNA DAN PEMBUDIDAYA TANAMAN JAHE DI KELURAHAN CISARUA KOTA SUKABUMI - Budilaksono, Sularso; Sovitriana, Rilla; Trisnawati, Nana; Maulana, Alifaqul; Dewi, Euis Puspita; Nasution, Evi Syafrida; Trikariastoto, ST; Effendi, Maya Syafriana; Yuliani, Nafisah (Universitas Mataram, 2024)
Sukabumi City is famous for MSMEs that make ginger candy. This MSME is located in RW 18, Cisarua Village, Sukabumi City. They have land for ginger plants but the ginger plants can only be harvested after they are 9 months old. The problem faced by PP is that PKK women, youth groups and ginger cultivators have not been able to process food and drinks made from ginger optimally. The main products of this village are currently only ginger candy and several processed ginger derivative products which are only in the trial stage. Training on processing food and drinks made from emprit ginger is a community service activity aimed at improving the skills and knowledge of the PKK group, Karangtaruna, and ginger plant cultivators in Cisarua Village, Sukabumi City. Emprit ginger, chosen as the main ingredient, has high nutritional value and health benefits. This training is expected to have a positive impact on the local economy and improve community welfare. It is hoped that processed food and beverage products made from ginger can become a mainstay of village products. This community service method uses lecture methods, practical demonstrations of making processed foods and drinks made from ginger and interviews. With this combination of qualitative methods, it is hoped that the training results will be maximized. The final result of the training was that PKK women, Karangtaruna and ginger cultivators were able to process ginger into various foods and drinks with high taste for sale and marketing. Participants can demonstrate how to prepare ginger-based dishes and drinks under the guidance of a team of community service presenters. This demonstration will be held on September 5-6 2023. This training was successful in increasing participants' knowledge and skills in processing emprit ginger into various kinds of food and drink products with economic value with the indicator that participants were able to process ginger into various foods and drinks with high selling value. The foods that were successfully made were various cakes, steamed cakes, cookies, jehe coffee, ginger chocolate, etc.